The Importance Of The Role And Attitude Of Nurses In Emergency Installations Towards The Implementation Of Triage In Optimal Health Services - Musiana, Musiana; Soamole, Maya Sari; Ishak, Sitti Nurhidayanti; Syahruddin, Nursita; Adiaksa, Baso Witman; Zaenal, Zaenal (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
Hospital is a complex organization, using a combination of special and complicated scientific tools, and functioned by various units of trained and educated personnel in dealing with and handling modern medical problems that are all bound by the same intention, for the recovery and maintenance of good health. The purpose of this study was to determine the relationship between the role and attitude of emergency nurses with the implementation of triage based on priority. The research method used was descriptive correlational with a cross-sectional design. The results of the study with the chi-square test p-value <0.05. The conclusion of this study is that there is a relationship between the role and attitude of emergency nurses with the implementation of triage based on priority. The researcher hopes that the results of this study can be used as a source of information and additional insight to carry out nursing actions even though there are still many shortcomings to be improved and adjusted to health services.